Anti‐tumour necrosis factor therapy enhances mucosal healing through down‐regulation of interleukin‐21 expression and T helper type 17 cell infiltration in Crohn's disease. (6th June 2013) - Liu, C.; Xia, X.; Wu, W.; Wu, R.; Tang, M.; Chen, T.; Xu, F.; Cong, Y.; Xu, X.; Liu, Z.
Summary: Anti‐tumour necrosis factor (TNF) monoclonal antibody (mAb) (infliximab, IFX) has been shown to be highly effective in the management of Crohn's disease (CD). Herein we investigated the potential role of IFX in inducing clinical remission and regulating interleukin (IL)‐21 expression and T helper type 17 (Th17) cell infiltration in the intestinal mucosa of CD patients. Twenty‐six CD patients were treated with IFX at weeks 0, 2 and 6. Clinical response, mucosal healing, serum C‐reactive protein (CRP) and erythrocyte sedimentation rate (ESR) were evaluated at week 10 after IFX administration. Expression of IL‐21, IL‐17A and retinoic acid‐related orphan receptor C (RORC) in intestinal mucosa were analysed by quantitative real‐time polymerase chain reaction (PCR) and immunohistochemistry. Peripheral blood and lamina propria CD4 + T cells were stimulated with anti‐CD3 and anti‐CD28 mAbs in the presence of IFX. Cytokine profiles and RORC were determined with enzyme‐linked immunosorbent assay (ELISA) and real‐time PCR. IL‐21 and Th17 cells were found to be expressed highly in inflamed mucosa of active CD patients compared with healthy controls. Ten weeks after IFX infusion, CD activity index, ESR, CRP and intestinal mucosal healing were improved markedly in CD patients, and IL‐21 expression and Th17 cell infiltration were decreased significantly compared with those before IFX therapy. In‐vitro study demonstrated that IFX treatment could suppress IL‐21, IL‐17A and RORC expression in cultured CD biopsies. Moreover, IFX was also observed to down‐regulate markedly IL‐17A, IL‐21 and RORC expression by CD CD4 + T cells. IFX is highly effective in inducing clinical remission and promoting intestinal mucosal healing in CD patients through down‐regulation of IL‐21 expression and Th17 cell infiltration in intestinal mucosa.